Challenges to Implementing and Sustaining Comprehensive Mental Health Program at Primary Health Care (PHC) In Wonogiri District, 2018 - Menikha Maulida; Suprio Heriyanto; Trisno Agung Wibowo (Berita Kedokteran Masyarakat (BKM), 2018)
Objective: Wonogiri District got the highest rank at Central Java Province for Mental Health Problem (MHP) as much as 6.7 per mile. This things become a public health problem/burden  because its provide damage not only to the health sector but also the others. So far, mental health has become the most neglected program. This study aimed to know the achievement and challenges for implementing and sustaining comprehensive mental health programs at PHC in Wonogiri District.Content: The achievement implementation of mental health program in Wonogiri District has not reached the target of minimum service standards. This was related to challenges for implementing the program about funding, there was no special budget allocation for mental health program at PHC. Existing problems were not only funding problems, but also human resources. There was only one psychiatrist in district and no psychologist at PHC. Only 5 of 21 mental health off icer (MHO) that had received training about mental health program and 50% of them were not report MHP regularly for every 6 months. Beside funding and human resources, the other results include the incomplete medicine supply in the district, the lack of attention to mental health in the national health and social sector targets, the lack of support from community and related to stigma, low socio-economic level with uninsured population, and the problem of district level supervision to PHC. Mental health problems will get worse if the program implemented has not been functioning optimally. Challenges in the implementation of mental health program were related to funding, resources, facilities and infrastructure, health surveillance, and self-motivation, health insurance, and supervision. Community support and social prescribing services can lead to improved sustainability.